Welfare and the welfare state: present and future - Greve, Bent (Abingdon, 2014)
"The welfare state plays a key role in people’s everyday lives in developed societies. At the same time, the welfare state is contested and there are constant discussions on how and to what degree the state should intervene, influence and have an impact on the development of society. Recent years have seen an accelerated transformation of the welfare state in the light of the global financial crisis, demographic change and changes in the perception of the state’s role in relation to social welfare. This raises fundamentally new issues related to social policy and welfare state analysis. This book provides: - an introduction to the principles of welfare - a conceptual framework necessary for understanding social policy at the macro-level - a comparative approach to welfare states globally - an overview of new ways to organise and steer welfare states - an introduction to welfare state politics and underlying economic framework - an account of equality and inequality in modern societies - new directions for welfare states The book’s focus on core concepts and the variety of international welfare state regimes and mechanisms for delivering social policy provides a much needed introduction to the rapidly changing concept of welfare for students on social policy, social studies, sociology and politics courses."